Null Expletives in Malay - Mustaffa, Amir Rashad (GEMA Online® Journal of Language Studies, 2020)
Malay is not known to have expletives due to their absence in the grammar, but this does not necessarily entail that expletives do not exist altogether. Gaps are observed in constructions with positions in which one would expect an expletive in a strictly non-pro-drop language such as English, hence making it seem as though Malay has a phonetically null variety of expletive. This phenomenon is common in attested pro-drop languages; however, data from Malay have not been properly documented and a principled account of the hypothesised existence of null expletives in Malay is lacking in the literature. This paper attempts to confirm whether Malay does have expletives by examining certain null-subject constructions through Chomsky’s (1982) Extended Projection Principle and comparing Malay with English and Irish. All cited examples in Malay are from the online archive of Utusan newspapers and those in Irish are from McCloskey (1991) and McCloskey (1996). All other examples are from consultants who are native speakers. It is found that Malay obeys the EPP, based on the obligatory movement of a subject into TP, which consequently makes it necessary for the use of a null expletive when no other constituent is able to raise to satisfy the EPP. The merging of a null expletive therefore creates an expletive-argument chain that causes the definiteness restriction in the existential construction, which can be overridden by substituting the expletive with clitic -nya on the verb.